2018
DOI: 10.1002/ejic.201801229
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Trivalent P‐Chloro‐Dithienophosphole and Its Reactivity with Organometallic Reagents

Abstract: P-chloro-dithieno[3,2-b:2′,3′-d]phosphole was synthesized and isolated from the reaction of an aminophosphole and HCl. Developed to act as a common starting material for Pfunctionalized phospholes, the compound exhibits a surprising reactivity by generating dimeric biphospholes. Despite this apparent sensitivity, when reacting with organolithium and Grignard reagents, a series of differently P-functionalized dithieno[3,2-b:2′,3′-d]phospholes was accessible. Unexpectedly, organolithium reagents showed reduced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…This implies that the bulky substituents affected the structures in the excited states. In the case of phospholes, it was reported that bulky substituents on the phosphorus atoms caused minor change in the absorption maxima, 18 but the effects on the structural relaxation were not discussed. To understand this phenomenon, the full geometries of 2 and 6 in their singlet excited (S 1 ) states were optimized at B3LYP/6-31G+(d,p), and were compared with those in their S 0 states (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the bulky substituents affected the structures in the excited states. In the case of phospholes, it was reported that bulky substituents on the phosphorus atoms caused minor change in the absorption maxima, 18 but the effects on the structural relaxation were not discussed. To understand this phenomenon, the full geometries of 2 and 6 in their singlet excited (S 1 ) states were optimized at B3LYP/6-31G+(d,p), and were compared with those in their S 0 states (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, compound 4 can be treated with organometallic reagents, such as Grignard and organolithium species, to afford dithienophospholes with a variety of P–R groups ( 5 , 5-O ) (Scheme ). …”
Section: Enhancing σ*−π* Interactions Through P–p Bond Formationmentioning
confidence: 99%